PERAN PENGAWAS PENDIDIKAN DAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU - T. Darmasah (JGK (Jurnal Guru Kita), 2021)
Abstract: The Role of Education Supervisors and Principals in Improving Teacher Professionalism. School supervisors and school principals as supervisors have a very strategic role in improving the quality of education in schools. Teachers are determinants of educational success through their performance at the institutional and experiential levels, so efforts to improve the quality of education must start from the teacher aspect. The purpose of this study was to determine: (1) the nature of teacher competence; (2) the Principal's role in improving teacher professionalism; (3) The role of supervisors in improving teacher professionalism. Methods This research uses a library research method by collecting a number of books, magazines, journals, life relating to the problem and research objectives. The results of the research The principal as a supervisor in the school has a very strategic role in improving the quality of education in schools, the principal as an education leader is to create a teaching and learning situation so that teachers can teach and students can learn well. In carrying out this role, the principal has a dual responsibility, namely carrying out school administration so as to create a good teaching and learning situation, and carrying out supervision so that teachersteachers increase in carrying out teaching tasks and inguide student growth. in improving the quality of teachers is the main and first step that must be done. In relation to improving the quality of teachers, the principal as the leader of a formal educational institution is the driving force, the determinant of school policy which will determine how the goals of schools and education, in general, are realized, including in improving the quality of teachers. Keywords: Education Supervisor, Principal, and Teacher Professionalism. Abstrak: Peran Pengawas Pendidikan Dan Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru. Pengawas sekolah dan Kepala sekolah sebagai supervisor memiliki peran yang sangat strategis dalam meningkatkan mutu pendidikan di sekolah, Guru merupakan penentu keberhasilan pendidikan melalui kinerjanya pada tataran institusional dan eksperiensial, sehingga upaya meningkatkan mutu pendidikan harus dimulai dari aspek guru. Tujuan penelitian ini dilakukan adalah untuk mengetahui: (1) Hakikat Kompetensi Guru; (2) Peran Kepala Sekolah dalam meningkatkan profesionalisme guru; (3) Peran Pengawas dalam meningkatkan profesionalisme guru.. Metode Penelitian ini menggunakan metode studi pustaka (library reseach) dengan mengumpulkan sejumlah buku-buku, majalah, jurnal, lifet yang berkenaan dengan masalah dan tujuan penelitian. Hasil penelitian Kepala sekolah sebagai supervisor di sekolah memiliki peran yang sangat strategis dalam meningkatkan mutu pendidikan di sekolah, putama kepala sekolah sebagai pemimpin pendidikan adalah menciptakan situasi belajar mengajar sehingga guru- guru dapat mengajar dan murid-murid dapat belajar dengan baik. Dalam melaksanakan peran tersebut, kepala sekolah memiliki tanggung jawab ganda yaitu melaksanakn administrasi sekolah sehingga tercipta situasi belajar mengajar yang baik, dan melaksanakan supervisi sehingga guru- guru bertambah dalam menjalankan tugas-tugas pengajaran dan dalam membimbing pertumbuhan murid-murid. dalam meningkatkan mutu guru merupakan langkah utama dan pertama yang harus dilakukan. Kaitannya dengan peningkatan mutu guru, kepala sekolah sebagai pemimpin suatu lembaga pendidikan formal merupakan motor penggerak, penentu kebijakan sekolah yang akan menentukan bagaimana tujuan sekolah dan pendidikan pada umumnya direalisasikan termasuk dalam peningkatan mutu guru. Keta Kunci: Pengawas Pendidikan, Kepala Sekolah dan Profesionalisme Guru